Biodiesel synthesis from used cooking oil via esterification-transesterification using jackfruit derived waste solid catalysts - Mulkan, Andi; Abd, Misswar; Kamarullah, Kamarullah (Politeknik Negeri Lhokseumawe, 2025)
The search for renewable and sustainable energy sources has heightened the significance of biodiesel. However, conventional production methods often rely on costly chemical catalysts that produce harmful waste, which this study addresses by introducing a low-cost, recyclable solid catalyst derived from abundant jackfruit peel waste in Indonesia. The novelty of this work lies in transforming underutilized biomass into a functional catalyst that improves both environmental sustainability and economic feasibility. Jackfruit peel was processed through cleaning, drying, grinding, open-air burning, and calcination at 500 °C for 120 minutes. The resulting material exhibited significant catalytic activity, with characterization confirming the presence of carbonates and metal oxides, particularly potassium (42.1%). Optimization of the transesterification reaction was carried out using a 1:9 molar ratio of oil to methanol, 12% catalyst loading, and a reaction temperature of 65 °C for 105 minutes. Under these conditions, the catalyst achieved a biodiesel yield of 98.9%. The produced biodiesel met the Indonesian National Standard (SNI 7182:2015) for key physicochemical properties. This research highlights the potential of agricultural waste as a sustainable catalyst source, offering an effective pathway toward cleaner biodiesel production and supporting circular economy practices in renewable energy development.